High‐resolution OLED display with remarkably low power consumption using blue/yellow tandem structure and RGBY subpixels. Issue 10 (19th October 2015) - Sasaki, Toshiki; Kataishi, Riho; Miyairi, Noriko; Kusunoki, Koji; Kaneyasu, Makoto; Miyake, Hiroyuki; Ohsawa, Nobuharu; Seo, Satoshi; Hirakata, Yoshiharu; Yamazaki, Shunpei; Ono, Koji; Cho, Takayuki; et al.
Abstract: A top‐emission organic light‐emitting diode (OLED) with a microcavity structure combined with a blue/yellow tandem structure was developed. A high‐resolution active‐matrix OLED display with the world's lowest level of power consumption using the tandem OLED with red, green, blue, and yellow subpixels was fabricated. Abstract : A top‐emission active‐matrix organic light‐emitting diode (AMOLED) with a microcavity structure combined with a B/Y tandem structure was fabricated. We have succeeded in reducing power consumption of the new AMOLED display by up to 40% as compared with that of a conventional one.